EDUCAÇÃO AMBIENTAL E RESÍDUOS SÓLIDOS: A IMPORTÂNCIA DA COOPERLIX PARA AMPLIAÇÃO DAS AÇÕES EDUCATIVAS E DE GERAÇÃO DE TRABALHO E RENDA PARA CATADORES DE RESÍDUOS SÓLIDOS RECICLÁVEIS E REUTILIZÁVEIS EM PRESIDENTE PRUDENTE - Alba Regina Azevedo Arana (Universidade do Oeste Paulista, 2010)
This research is integrated with the actions that have been developed by several partner institutions. The central objective is to leverage the COOPERLIX expansion of educational and employment and income generation for collectors of solid waste recycled and reused in Presidente Prudente. They performed several actions: study meetings and planning, and cartographic literature, implementation, tabulation and analysis of questionnaires, systematization of data and information, development of teaching materials, organization and execution of activities and educational campaigns. As a result we obtained the inclusion of new pickers in the dump Cooperlix, greater social participation in the selective disposal, improvement of quality and quantity of waste collected, educations and training of university.